2020
DOI: 10.1002/fsn3.1885
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cudrania tricuspidata on anti‐senescence in high glucose‐treated endothelial cells via the Akt/p53/p21 pathway

Abstract: Vascular complications significantly contribute to the incidence of diabetes mellitus and the associated mortality (Brownlee, 2005). The major causes of vascular complications in diabetes are endothelial dysfunction and hyperglycemia related to damaged neovascularization (Sheetz & King, 2002). Endothelial dysfunction is a major cause of atherosclerosis development; therefore, it is important that the vessels are healthy to lower the risk of cardiovascular complications associated with diabetes mellitus (Kinlay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that the fruit, leaves, and roots of CT also have various biological activities, including antioxidant [ 50 , 51 ], anti-inflammatory [ 52 ], antiobesity [ 53 ], hepatoprotective [ 54 ], and neuroprotective [ 16 , 55 ] effects. It has recently been reported that CT displays antisenescence effects on endothelial cells exposed to high glucose, a major diabetic factor [ 56 ]. In addition, renal protective effects have been reported for cudratricusxanthone A, an active component of CT, in cecal ligation and puncture-induced septic mice [ 17 ]; however, the effects of CT on DN have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the fruit, leaves, and roots of CT also have various biological activities, including antioxidant [ 50 , 51 ], anti-inflammatory [ 52 ], antiobesity [ 53 ], hepatoprotective [ 54 ], and neuroprotective [ 16 , 55 ] effects. It has recently been reported that CT displays antisenescence effects on endothelial cells exposed to high glucose, a major diabetic factor [ 56 ]. In addition, renal protective effects have been reported for cudratricusxanthone A, an active component of CT, in cecal ligation and puncture-induced septic mice [ 17 ]; however, the effects of CT on DN have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…2017 ; Choi et al. 2020 ; Kim and Park 2020 ; Lee and Choi 2020 ). However, the complete plastomes of Maclura have not been reported.…”
mentioning
confidence: 99%